Association between blood pressure multi-trajectory and cardiovascular disease among a Chinese elderly medical examination population - Chen, Quan; Du, Jinling; Hong, Xin (Frontiers in Cardiovascular Medicine, 2024)
• Longitudinal data for systolic blood pressure and diastolic blood pressure have been modeledto identify four distinct multivariate trajectories of blood pressure function in older Chinese adults. • Higher level multi-trajectories groups had a significantly increased risk of cardiovascular disease.The trajectory of high level in blood pressure has an increased risk of suffering from cardiovascular disease, indicating the importance of preventing blood pressure rising to maintain the quality of life in older adults.